2017
DOI: 10.1080/1828051x.2017.1364984
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cultivar, wilting and storage period on fermentation and the clostridial community of alfalfa silage

Abstract: The objective of this study was to gain deeper insights into chemical transformations and the clostridial community dynamics during the ensiling of alfalfa. A factorial experiment was conducted with four alfalfa cultivars [Sanditi (A1), AC Caribou (A2), WL319HQ (A3) and 4030 (A4)] Â three wilting durations [0 h (direct-cut), 2 h and 4 h] Â three storage periods (14, 28 and 56 days). The clostridial community was examined using denaturing gradient gel electrophoresis. High butyric acid and ammonia nitrogen (NH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
28
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 34 publications
10
28
2
3
Order By: Relevance
“…This may be because low pH value can lead to the acid hydrolysis of fibre [20] and inhibit the growth of undesirable bacteria [3]. This result was in agreement with the study of Zheng et al [5], who concluded that a low DM content always coupled with low WSC, and this is readily subjected to clostridial fermentation.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This may be because low pH value can lead to the acid hydrolysis of fibre [20] and inhibit the growth of undesirable bacteria [3]. This result was in agreement with the study of Zheng et al [5], who concluded that a low DM content always coupled with low WSC, and this is readily subjected to clostridial fermentation.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, wilting had significant effects on the CP and BC in this study. The CP content in the wilted material was lower than that in the non-wilted material, and this result is similar with the finding of Zheng et al [5]. The reason might be that the plant cells still survived after harvesting, and the degrading enzymes in cells degraded the proteins into small molecules of ammonia during wilting [15].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations